THE DETERMINATION OF SERUM IRON AFTER THE INTRAVENOUS INJECTION OF IRON-DEXTRAN - Webster, D. (1960)
A rapid technique for the determination of iron in serum, after the intravenous injection of iron-dextran, is presented. Dithionite is used for the reduction of ferric to ferrous iron. The use of a detergent solution enables protein precipitation to be omitted. The iron reagent, 4: 7-diphenyl-1: 10-phenanthroline, and its ferrous complex are both soluble in the dilute detergent solution. Lipaemic serum can be used without affecting the results. The recovery of added ferric iron, as iron-dextran, is quantitative.